An Alternate Route to Teaching - Kirsten Limpert (The Advocate, 2011)
Introduction: Alternate route to teacher certification typically refers to programs that permit people with non-education bachelor degrees the option to earn a teaching license. This route allows people to enter the teaching field without returning to a college campus for two years of coursework and student teaching to obtain a license.